Strategi Perpustakaan Umum Dalam Meningkatkan Literasi Budaya Masyarakat - Winastwan, Rheza Ega; Fatwa, Annisa Nur (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2021)
Public libraries as information institutions that are obliged to meet the information needs of the community, have a central and representative role in efforts to increase public literacy, especially in terms of cultural literacy. The discourse on cultural literacy has received less attention from academics in the field of libraries and information. This article will discuss about strategies that can be carried out by public libraries in order to improve people's cultural literacy. This study uses a qualitative method with a descriptive approach. This article is a literature study by utilizing various reference sources to obtain data and the author's thoughts as outlined in this article. The results show that there are three efforts that can be made by public libraries in order to improve the cultural literacy of the society, including providing special library services that contain local content collections, holding local cultural nuanced activities, and collaborating with other agencies in order to continue to improve the cultural literacy of the society.